Desenvolvimento de simuladores renais para uso em medicina nuclear - Dullius, Marcos Alexandre (2014)
Quality control programs in nuclear medicine include verifying the efficiency of all equipment used for diagnosis and therapy, including scintillation cameras. To that end, we have developed and evaluated the performance of four phantom kidneys two static anthropomorphic, one semi-dynamic, and one dynamic to acquire static and dynamic renal scintigraphic images. The static anthropomorphic phantoms were used to characterize and evaluate the response of the processing system for different concentrations of radionuclides through static renal scintigraphy images (99mTc-DMSA), obtained with posterior, right posterior oblique, left posterior oblique, and anterior incidences. The static phantoms were made in two ways; one was made of acrylic from a mold of a pair of human kidneys preserved in formalin, and the second was built with acrylonitrile butadiene styrene (ABS), in a 3D printer using the Slicer program, based on a computed tomography (CT) of the thorax, using the Slicer program. The semi-dynamic and dynamic phantoms were constructed to characterize and evaluate images of dynamic renal scintigraphy. In the semi-dynamic phantom, the injection of radiotracer was performed manually, whereas in the dynamic phantom, the radiotracer was automatically injected through an injector system. With the semi-dynamic phantom, it was possible to analyze the formation of a renogram with normal renal scintigraphic appearance using an imaging system. The simulations obtained from the dynamic phantom simulator enabled studies of normal renal scintigraphy and four other forms of renograms. The static anthropomorphic phantom kidneys proved to be efficient for use in evaluations of varying concentrations of radionuclides. The dynamic phantom kidney was useful for analysis of scintigraphic images and obtaining different pathways for elimination of the radioisotope, allowing for analysis of different renograms. Therefore, the new kidney phantoms would be useful for quality control of image processing systems in renal scintigraphy.